VIRAL-HOST INTERACTIONS: DECODING IMMUNE RESPONSE AND MOLECULAR DIAGNOSTICS FOR EMERGING INFECTIOUS DISEASES (Journal of Medical & Health Sciences Review, 2025)
Emerging infectious diseases (EIDs) driven by viral pathogens continue to challenge global health, necessitating a profound understanding of viral-host interactions and advanced diagnostic tools. This review explores the molecular interplay between viruses and host immune systems, emphasizing innate and adaptive immune responses, viral evasion strategies, and host genetic influences on disease outcomes. Zoonotic spillover, fueled by ecological disruptions, is a key driver of EIDs, with examples like SARS-CoV-2 and Ebola highlighting the need for robust surveillance. Molecular diagnostics, including real-time PCR, next-generation sequencing (NGS), and CRISPR-based platforms, have revolutionized pathogen detection, enabling rapid and precise responses. Challenges such as viral evolution, diagnostic accessibility, and global surveillance gaps persist, underscoring the need for innovative solutions. This article integrates insights from virology, immunology, and diagnostics to propose strategies for mitigating EIDs. Future directions include universal diagnostics, AI-driven predictive models, and mRNA-based vaccines to enhance preparedness. By decoding viral-host dynamics, this review aims to guide researchers and policymakers in addressing the growing threat of EIDs in a globally interconnected world.